Active and durable alkaline earth metal substituted perovskite catalysts for dry reforming of methane - Dama, Srikanth; Ghodke, Seema R.; Bobade, Richa; Gurav, Hanmant R.; Chilukuri, Satyanarayana (Applied Catalysis B - Environmental, 2018)
Dry reforming of methane is an important process for the utilization of CO2 and to get valuable synthesis gas. Alkaline earth metal substituted MZr1-xNixO3-delta perovskites were synthesized by citrate gel method, characterized and evaluated for dry reforming methane. Characterization results show that the type of alkaline earth substituted at the A site of the perovskite oxide plays an important role in terms of structure, basicity, oxygen deficiency and Ni dispersion. Calcium substituted CaZr0.8Ni0.2O3-delta catalyst shows superior activity in terms of high CH4 and CO2 conversion, while maintaining the activity even after 500 h of reaction. Mechanistic investigations were carried out using transient pulse experiments and insitu FTIR-diffuse reflectance spectroscopy. These experiments reveal that redox property and basicity play important role in activation and sustaining the reforming reaction. Insitu FTIR measurements show that surface hydroxyl groups of the support are vital for high activity and durability of CaZr0.8Ni0.2O3-delta catalyst. XRD and TGA analysis of catalysts after reaction show the structures are retained, but peaks pertaining to coke were observed on SrZr0.8Ni0.2O3-delta and BaZr0.8Ni0.2O3-delta catalysts. On the otherhand, CaZr0.8Ni0.2O3-delta catalyst had only amorphous carbon even after 500 h of reaction. HRTEM studies revealed that SrZr0.8Ni0.2O3-delta and BaZr0.8Ni0.2O3-delta catalysts deactivated mostly due to the formation of carbon nanotubes with Ni embedded in them. Raman and XPS analysis helped in identifying types of coke precursors present on the catalysts. The investigation also illustrate that type of carbon formed depends on the basicity of perovskite oxide, metal to support interaction, Ni crystallite size, surface hydroxyl groups and oxygen defects. This study clearly demonstrated that CaZr0.8Ni0.2O3-delta is an excellent catalyst for dry reforming reaction with long life.

Effect of B site substitution in Gd2B2-xNiyO7-delta (B= Ti, Zr) ternary metal oxide catalysts in dry reforming of methane - Ghodke, Seema R.; Thundiyil, Shibin; Dongapure, Pavan; Devi, R. Nandini (Molecular Catalysis, 2022)
Structured catalysts are emerging as active and durable catalysts in dry reforming of methane due to their inherent characteristics like lattice insertion of active metals and consequent stability imparted. Here we report Ti and Zr substituted Gd2B2-xNiyO7-delta (B = Ti, Zr) catalysts synthesized by citrate gel method, which are characterized and tested for dry reforming of methane. Structure and Ni substitution has been confirmed by Rietveld refinement of powder XRD patterns and Raman analysis. TPR and CO2-TPD were performed to analyze the reducibility and effect of basic sites of catalysts in DRM activity. Ni doped Ti analogue shows stable and superior activity towards dry reforming of methane for 100 h. The in situ IR studies and XPS analysis confirmed the presence of surface hydroxyl species in this catalyst, which triggers the activation of CO2 and provides higher and durable activity in dry reforming reaction. Absence of any C formation in this catalyst after durability test indicates the mechanism of C gasification by the surface hydroxyl species enhancing stable activity for long durations.
Keywords: A(2)B(2)O(7); Citrate gel method; Dry reforming of methane; Ternary metal oxide

Coke management: unveiling the role of Ce substitution in Gd2Zr1.8Ni0.2O7-δ catalyst for dry reforming of methane - Ghodke, Seema R.; Mule, Harshada M.; Bhatkar, Akash; Devi, R. Nandini (Energy & Fuels, 2025)
The redox characteristics of cerium have become crucial elements in the carbon gasification process during methane dry reforming. This work examines the effect of cerium substitution in the Gd2Zr1.8Ni0.2O7-delta catalyst during methane dry reforming, employing a range of Ce-substituted Gd2Zr1.8-x Ni0.2Ce x O7-delta (x = 0.1, 0.2, 0.5, 0.75) catalysts synthesized via the citrate gel method. The materials crystallized in a fluorite structure, as verified by X-ray diffraction analysis and Raman spectroscopy. Enhanced reducibility of the substituted catalysts was assessed through H2-temperature-programmed reduction analysis. CO2 and O2 desorption studies along with X-ray photoelectron spectroscopy validated the enhanced basicity and generation of active oxygen and hydroxyl species. The enhanced activity and coke gasification in Gd2Zr1.6Ni0.2Ce0.2O7-delta catalyst are attributed to surface hydroxyl species, and prominent intermediate carbonate and bicarbonate species were further verified by in situ infrared spectroscopy. The high basicity of the Gd2Zr1.6Ni0.2Ce0.2O7-delta catalyst and high concentrations of oxygen vacancies (similar to 66.4%) enhances CO2 adsorption and desorption, resulting in continuous CO2 activation, leading to less carbon formation and superior activity of the catalyst. The Gd2Zr1.6Ni0.2Ce0.2O7-delta catalyst exhibits the highest CH4 and CO2 conversion rates, at 85% and 93.5%, respectively, and remains stable for 100 h. Postreaction analysis of Gd2Zr1.6Ni0.2Ce0.2O7-delta confirms structure stability and less carbon formation compared to other substituted catalysts in dry reforming of methane. This study demonstrates that the moderate concentration of Ce in the Gd2Zr1.6Ni0.2Ce0.2O7-delta catalyst exhibits balanced activity and coke gasification capacity in the dry reforming of methane for a longer duration.

Modulation in surface properties by Ni doping in Na2Ti3O7: effect on dry reforming of methane - Ghodke, Seema R.; Devi, R. Nandini (ACS Applied Engineering Materials, 2025)
Dry reforming of CH4 using CO2 is considered as an excellent process for converting two greenhouse gases to platform chemicals. However, the challenge is severe coking as well as sintering and consequent deactivation in the absence of steam as in the more prevalent steam reforming. Here, we present a layered Ti-based oxide with appropriate basicity to facilitate CO2 adsorption and active metal Ni incorporated in the lattice sites to minimize sintering. Ni-doped Na2Ti3O7 was synthesized using the sol–gel method and subsequently characterized and screened in dry reforming of methane. Characterization results indicate the successful formation of the monoclinic phase of Na2Ti3O7. The variant Na2Ni0.2Ti2.8O7, which contains a higher concentration of Ni, exhibited improved reducibility and basicity, as determined through H2-TPR and CO2-TPD analysis. The presence of hydroxide, carbonate, and bicarbonate species was confirmed via X-ray photoelectron spectroscopy (XPS) and diffuse reflectance infrared Fourier transformation (DRIFT) studies, leading to increased conversion of CH4 and CO2 over extended periods with the Na2Ti2.8Ni0.2O7 catalyst. Basic Ti–OH groups replenished under reaction conditions may play a vital role in reducing coke formation in this catalyst. Post-reaction characterization revealed phase transformations in low Ni content catalysts, as evidenced by X-ray diffraction (XRD) and RAMAN analysis. Additionally, the suppression of coke formation and morphological changes were assessed through thermogravimetric analysis (TGA) and field emission scanning electron microscopy (FESEM) analyses in Na2Ti2.8Ni0.2O7 catalyst, respectively. The study highlighted the significant influence of elevated Ni concentrations on phase stability and conversion efficiency in the dry reforming of methane. This also evidences the importance of defects created by appropriate doping, which modulates the surface properties facilitating coke gasification.